Thermodynamic feasibility evaluation of hybrid dehumidification – mechanical vapour compression systems. (1st March 2018) - Thu, K.; Mitra, S.; Saha, B.B.; Srinivasa Murthy, S.
Graphical abstract: Highlights: Breakeven COP for the coupled dehumidifier of dehumidifier + MVC system is evaluated. MVC at higher Tchilled is studied using Carnot, endoreversible and ideal cycle methods. Three refrigerants (HFC-R134a, HFC-R32 and HFO-R1234yf) for MVC are analysed. The coupled dehumidifier needs COP at least 4 to batter conventional MVC systems. LCC_NPV affirms separate dehumidifier is viable for low outdoor air ratio operations. Abstract: Air conditioning approach using two separate units for latent heat and sensible heat removal opens up opportunities and challenges for improved efficiency. In such systems, the dehumidification device removes moisture from the air stream usually without condensation whilst the remaining sensible load is handled by a conventional mechanical vapour compression (MVC) machine. This article investigates the thermodynamic feasibility of such hybrid dehumidifier + MVC systems as potential replacements for the conventional MVC devices. We shed some light on the minimum efficacy requirement in terms of COP or simply the breakeven COP for the coupled dehumidification system. Thermodynamic investigation has been conducted using classical Carnot, endoreversible technique and the experimental approaches. The breakeven COPs for a dehumidifier + MVC system where the latter using HFC-R14a, HFC-R32 and HFO-R1234yf as refrigerants have been investigated at assorted outdoor air ratios. Performance enhancement in terms of COP and the cooling capacity at elevated temperatures for sensible cooling are accounted for. It is observed that the breakeven COP for the dehumidification system ranges from 9 to 17 (Carnot approach) and 4.3 to 6.8 (Ideal cycle) in order to be realistically competitive with the current efficiency offered by a MVC system for the both dehumidification and sensible cooling. The life cycle cost (LCC) analysis is further performed to assess the fresh air-handling systems using a conventional MVC system and a dehumidifier + MVC system. The unprecedented improvement in the performance of the MVC systems further raises the ceiling for the breakeven COP of the dehumidification systems.